DC/DC converter to power spectral lamps - M. Yu. Nikolshin; A. V. Frunze; V. K. Bityukov (Российский технологический журнал, 2023)
Objectives. The paper describes the creation of a DC/DC converter for powering hollow cathode lamps widely used currently as highly stable sources of spectral lines in spectral absorption analyzers and other applications. Typically, mains power supplies are used for such lamps, since installations using hollow cathode lamps are manufactured as stationary. However, there are no principal obstacles to manufacturing portable versions by simply substituting the power supply. However, special attention should in this case be paid to the power supply of the spectral lamp itself, since the amplitude stability of the radiation depends on the smoothness of its supply voltage. Therefore, the development of the pulse DC/DC converter with high efficiency and low rippling is a relevant and expedient problem.Methods. The set task is solved by methods of mathematical calculations, circuit simulation in LTSpice XVII сomputer-aided design system, and experimental verification.Results. The structural and principal electrical circuit of a prototype converter is developed on the basis of a topological analysis of pulse DC/DC converters, along with its calculations and simulation, and a printed circuit board. The developed autonomous high-voltage DC/DC converter has a low ripple level (~250 mV) of the output voltage (~491 V) at a load current of ~20 mA to ensure highly stable radiation.Conclusions. The possibility of obtaining a high voltage when using the topology of a step-up DC/DC converter with a choke is demonstrated. The experimental verification confirmed the correctness of calculations and modeling of a high-voltage DC/DC converter for powering hollow cathode spectral lamps.